The Mechanism of Activated Nitrogen-Containing Metabolites in the Respiratory Tract: Proinflammatory Effect (Part 3) - O.Ye. Abaturov; A.P. Volosovets; O.Ye. Khudyakov (Zaslavsky O.Yu., 2016)
The literature review presents current data about modulating action of nitrogen monoxide on the inflammatory response and the apoptotic process depending on its concentration. There is demonstrated a dual action of nitric oxide in the respiratory tract - prevention of infection and strengthening the destruction of lung tissue.